„Licht ist das sicherste Bombenziel". Przyczynek do badań nad zaciemnianiem źródeł światła w Festung Breslau w 1945 roku - Rosner-Leszczyński, Kacper (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
This article focuses on obligations related to blackout which were imposed on the inhabitants of Festung Breslau. It analyzes documents issued by the Fortress Command, the local press (Schlesische Tageszeitung), and written relations in the form of memoirs and diaries. All of these were collected by Horst Gleiss in the source edition Breslauer Apokalypse 1945.
Keywords: blackout; air raids; civilians; lighting; Festung Breslau